Cardiorespiratory effects of isoflurane and medetomidine–tiletamine–zolazepam in 12 bonobos (Pan paniscus). (24th January 2023) - Bucknell, Pip; Dobbs, Phillipa; Martin, Mike; Ashfield, Samantha; White, Kate
Abstract: Background: Cardiovascular disease is a significant cause of mortality in captive great apes. However, data from bonobos are lacking due to a paucity of collections in Europe. Comprehensive preventive screening is required to understand the aetiopathogenesis of cardiovascular disease, but the provision of a stable and predictable anaesthetic protocol with minimal cardiovascular effects is challenging. Methods: This prospective, observational case series reports anaesthesia of 12 bonobos using hand‐injected medetomidine and tiletamine–zolazepam followed by maintenance with isoflurane in oxygen. Comprehensive clinical examinations, including arterial blood gases and echocardiography were undertaken. Results: Induction of anaesthesia with hand injection was successful in all but one individual. Respiratory acidosis with metabolic alkalosis and respiratory alkalosis with metabolic acidosis were documented. Hypochloraemia may have contributed to non‐respiratory alkalosis in one individual. Ten bonobos experienced hypotension and required haemodynamic support. Both N‐terminal pro b‐type natriuretic peptide and troponin I cardiac biomarkers correlated with left ventricular ejection fraction (percentage). Recovery was smooth, rapid and uneventful in all animals. Limitations: The effects of the anaesthetic must be considered during echocardiographical interpretation. Conclusions: The anaesthesia protocol provided a safe, predictable induction and recovery, facilitating diagnostics (including echocardiography) and minor surgical procedures. Comprehensive monitoring, including invasive blood pressure monitoring and haemodynamic support, is highly recommended.